2015
DOI: 10.1038/gt.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of AAV-DJ pseudoserotype expressing COX2 provided early onset of transgene expression and promoted bone fracture healing in mice

Abstract: We have previously obtained compelling proof-of-principle evidence for COX2 gene therapy for fracture repair using integrating retroviral vectors. For this therapy to be suitable for patient uses, a suitable vector with high safety profile must be used. Accordingly, this study sought to evaluate the feasibility of AAV as the vector for this COX2 gene therapy, because AAV raises less safety issues than the retroviral vectors used previously. However, an appropriate AAV serotype is required to provide early incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…Third, a deficiency of M1 macrophage-recruiting molecules (i.e., monocyte chemoattractant protein 1 receptor, also known as C-C motif chemokine receptor 2 [CCR-2]), led to compromised fracture healing (40). Fourth, cyclooxygenase 2 (COX-2) gene therapy accelerated fracture healing (41)(42)(43), and inhibitors of COX-2 compromised fracture healing primarily at the proinflammatory phase of fracture healing (44). This role of COX-2 in fracture repair is at least partially related to M1 macrophages because M1 macrophages depend on COX-2 to enhance in vitro osteoblast differentiation in MSCs (13).…”
Section: Discussionmentioning
confidence: 99%
“…Third, a deficiency of M1 macrophage-recruiting molecules (i.e., monocyte chemoattractant protein 1 receptor, also known as C-C motif chemokine receptor 2 [CCR-2]), led to compromised fracture healing (40). Fourth, cyclooxygenase 2 (COX-2) gene therapy accelerated fracture healing (41)(42)(43), and inhibitors of COX-2 compromised fracture healing primarily at the proinflammatory phase of fracture healing (44). This role of COX-2 in fracture repair is at least partially related to M1 macrophages because M1 macrophages depend on COX-2 to enhance in vitro osteoblast differentiation in MSCs (13).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of non-pathogenicity and efficient persistence of AAVs makes it an attractive delivery vehicle for gene therapy applications24. To date, twelve naturally occurring human AAV serotypes25 and more than one hundred serotypes from non-human primates and other species have been discovered2627. The identification of novel serotypes, such as AAV9 and AAVrh10, directed under the action of various promoters, as well as the repertoire of engineered chimera vectors, are likely to improve and enlarge the AAV application range222829.…”
Section: Discussionmentioning
confidence: 99%
“…To identify which cells were infected with AAV, 25 µl AAV-GFP diluted with saline was injected into putamen of cynomolgus monkey unilaterally. As it is described already, AAV-DJ has been widely used for the vehicle of the gene delivery because it has a higher transduction efficiency [ 11 ]. Therefore, we packaged with AAV-DJ.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the authors found that AAV serotype 5 displayed the most efficient transduction of neurons in this brain region. Recently, AAV-DJ vector was generated as one of the recombinogenic hybrid vector from gene shuffling of eight serotypes and has been widely used across a broad range of cell types because it has a higher transduction efficiency both in vitro and in vivo [ 10 11 ]. Even though AAV serotype 5 displayed the most efficient transduction of neurons in the African green monkey brain region [ 9 ], AAV-DJ has not been tested in the primate.…”
Section: Introductionmentioning
confidence: 99%